Application of genetic problem base online discussion to improve genetic literacy of prospective teachers - Yuyun Maryuningsih; Topik Hidayat; R. Riandi; Nuryani Y. Rustaman (JPBI (Jurnal Pendidikan Biologi Indonesia), 2022)
Genetics is a subject that is quite difficult according to students. Various strategies and methods are used to understand genetics in learning to have genetic literacy. One way of increasing genetic literacy in students is to apply genetic problems based on an online discussion in genetics lectures. The research was conducted to determine the effect of genetic problem-based online discussion on increasing students' genetic literacy. The research design used a pre-posttest control group design. It was carried out experimentally on three treatment groups: the genetic problem base of students, the genetic problem base of educators - students, and the genetic problem base of educators. According to the genetic literacy domain, genetic literacy is measured through multiple-choice tests, including genetic models, meiotic models, and molecular models. Manova analyzed the value of gene literacy, and a post-doc further test was performed to differentiate genetic literacy in the three treatment groups. The results showed that genetic literacy increased in all treatment groups, with the highest increase in the group that applied a genetic problem base focused on student problems.